ACER’s Global Logistics and Innovations: Total Costs Perspectives - Ming-Yuen Tarng,; Po-Young Chu,; Jau-Shin Hon, (Asian Academy of Management Journal, 1998)
ACER’s Global Logistics and Innovations: Total Costs Perspectives(PDF not available)